Analysis of the Suitability and Supporting Capacity of Mangrove Ecotourism in Yenelo Lake, Sagea Village, North Weda District, Central Halmahera Regency - M. Abjan Fabanjo; Nursanti Abdullah (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
The mangrove area around Lake Yonelo is a unique and potential area, but the area tends to be threatened by increasing mining activities in the area. Management of the mangrove area around Lake Yenelo as an ecotourism area is an alternative form as an innovative effort to maintain environmental functions as a provider of environmental services in order to remain sustainable. The purpose of this study was to determine the suitability of the tourist area and the carrying capacity of the area as well as the types of activities in the mangrove ecotourism area. The method used is a survey method, using the analysis of the tourism suitability index (IKW) and the carrying capacity of the area (DDK). The results of the analysis of the suitability index of the Yenelo Lake area are classified as very suitable for developing mangrove ecotourism activities, while the results of the analysis of the carrying capacity of the area are 412 people/day with the carrying capacity of the utilization of 42 people/day with the types of activities, namely tracking, picnicking, sitting relaxed, photography and education in along 844 m of mangrove area. The contribution of this type of activity will provide new job opportunities for the community around the mine which will certainly affect the welfare level of the community around the mine in the North Weda District.